MOXIBUSTION: A REVIEW OF THE LITERATURE (Fiep Bulletin - online, 2013)
Traditional Chinese Medicine is the art of preventing and treating diseases, through natural means. Originated in China there are about five thousand years and it has several therapeutic resources, but the most known are the Acupuncture, the Phytotherapy and the Moxibustion. Moxibustion is a therapeutic method which aims to use certain substances or herbs to heat acupuncture points or areas of the body to be treated. The heat resulting from this process produces stimuli that regulate the physiological functions, through the meridians. The feedstock most used to make the moxibustion is the leaft of the plant Artemisia vulgaris. There is a major lack of bibliographic materials that could support the research with moxibustion. Therefore, this study aimed to do a bibliographic review about the moxibustion technique, describing the therapeutic action of the herb Artemisia vulgaris and reporting some studies about the moxibustion with scientific correlations. Through of the study observed that the literature about the subject restricted to the Treated Chinese Medicine and the scientific research are scarce. However, it was possible through this review, gather a lot of informations about the technique of the moxibustion, and suggest more urgent studies about this subject, to elucidate further the technique.
Keywords: moxibustion; artemisia; acupuncture